2018
DOI: 10.1242/jcs.202895
|View full text |Cite
|
Sign up to set email alerts
|

F-box proteins Pof3 and Pof1 regulate Wee1 degradation and mitotic entry in fission yeast

Abstract: The key cyclin-dependent kinase Cdk1 (Cdc2) promotes irreversible mitotic entry, mainly by activating the phosphatase Cdc25 while suppressing the tyrosine kinase Wee1. Wee1 needs to be downregulated at the onset of mitosis to ensure rapid activation of Cdk1. In human somatic cells, one mechanism of suppressing Wee1 activity is mediated by ubiquitylation-dependent proteolysis through the Skp1/Cul1/F-box protein (SCF) ubiquitin E3 ligase complex. This mechanism is believed to be conserved from yeasts to humans. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
1
4
0
1
Order By: Relevance
“…As shown in Figure 3A , CDCA3 and its related DEGs are involved several diverse biological processes, such as nuclear division and mitotic nuclear division. Qiu [ 42 ] reported that CDCA3 is involved in cell mitosis, validating our results. A GSEA indicated that CDCA3 is related to various gene sets, such as E2F targets, spindle formation during mitosis, KRAS signaling, and G2M checkpoints ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As shown in Figure 3A , CDCA3 and its related DEGs are involved several diverse biological processes, such as nuclear division and mitotic nuclear division. Qiu [ 42 ] reported that CDCA3 is involved in cell mitosis, validating our results. A GSEA indicated that CDCA3 is related to various gene sets, such as E2F targets, spindle formation during mitosis, KRAS signaling, and G2M checkpoints ( Figure 4 ).…”
Section: Discussionsupporting
confidence: 90%
“…E2F4 promotes proliferation and cell cycle progression in hepatocellular carcinoma cells by up-regulating CDCA3 expression [ 43 ]. Numerous studies have shown that CDCA3 is related to cell mitosis [ 36 , 42 ]. These results confirmed the results of the GSEA in present study.…”
Section: Discussionmentioning
confidence: 99%
“…Published articles about CDCA3 mainly focused on the role of CDCA3 in cell cycle regulation and drug resistance in digestive tumours and lung cancer 24,41 . It has been reported that CDCA3 functions as an F-box protein that leads to the ubiquitylation-dependent proteolysis of Wee1 and ultimately results in irreversible mitotic entry 42 . In our research, we found for the first time that CDCA3 upregulated by SNHG12/SP1 was related to RCC and was involved in sunitinib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…During M-phase, ubiquitin-dependent protein degradation is responsible for the downfall of WEE1. Initially, during the G2-M transition, PLK1, CDK1, and CK2 phosphorylation at S53, S123, and S121 residues generate phosphodegrons (PDs), and CDC34 ubiquitination of WEE1 allows SCF (skp1/cul1/F-box) β-TrCP (β-transduction repeat-containing protein), Tome-1 (trigger-of-mitotic-entry 1), Smurf1 (Smad ubiquitination regulatory factor1), and Pof1/3 (Promoter of Filamentation1/3) (in fission yeast) mediated WEE1 degradation. However, in a later study, WEE1 was found to interact with the β-subunit of CK2, but this interaction showed no remarkable influence on WEE1 kinase activity . Another mechanism reported is the nuclear export of WEE1.…”
Section: Introductionmentioning
confidence: 99%